Investigation of Innovation during Bid Evaluation Process in the Road Construction Industry - Pardeep Kumar Oad; Stephen Kajewski; Arun Kumar; Bo Xia (Salehan Institute of Higher Education, 2021)
Tender evaluation is the procedure of choosing the best contractor for a particular project from many applicants. Although rational and logical methods can be used for bidding strategies, bid evaluation remains a skill for which an engineer’s verdict is crucial. Contractors commonly witness that tender selection is not an easy job, and the lowest bid does not necessarily win the contract. The tender decision mainly depends on quantifiable measures such as financial costs and paybacks, and qualitative or invisible factors like administrative security accountability, aptitude, and the proficiency of the contractors. Moreover, Bid evaluation is a decision-making procedure that incorporates an extensive criteria range for which the information is not accordingly. Hence, ambiguity linked to such information is not appropriate for this study. This paper aims to evaluate innovation during the bid evaluation process in the road industry. The research results indicate that the private and public sectors in Australia offer innovative products and work methods, given the chance. Therefore, innovation during the bid evaluation process is welcomed and sometimes strongly encouraged. Further, it is important to have strong research in to how to effectively determine value for money in the context of developing suitable and quality roads. Therefore, this research is useful in the context of evaluating factors that help to understand value for money in the road sector in context of bid evaluation process. Doi: 10.28991/cej-2021-03091676 Full Text: PDF